The curriculum question in doctoral education - González-Ocampo, Gabriela (2016)
The landscape of doctoral education has changed immensely during the last decades. Different transnational policies, different publics, different purposes and different academic careers all contribute to the need for a new understanding of this under-researched field. Our focus is on explicit curriculum analysis to undertake intentional and meaningful change, especially in terms of the processes and outcomes of doctoral education. We draw on research on doctoral education, as well as the emerging literature on early career researchers (ECRs) and on professional learning, and consider how the concept of curriculum can help us think differently about doctoral education, particularly in relation to processes and outcomes. Finally, we suggest a research agenda for developing the curricula of doctoral education.